Diachronous seawater retreat from the southwestern margin of the Tarim Basin in the late Eocene. (February 2016) - Sun, Jimin; Windley, Brian F.; Zhang, Zhiliang; Fu, Bihong; Li, Shihu
Highlights: New chronology of the Cenozoic marine–terrestrial strata in the Tarim Basin. Diachronous seawater retreat from the southwestern margin of the Tarim Basin. Seawater retreat was dominantly controlled by regional tectonics. Abstract: In contrast to the present hyper-arid inland basin surrounded by the high mountains of Central Asia, the western Tarim Basin was once connected with the Tajik Basin at least in the late Eocene, when an epicontinental sea extended from the western Tarim Basin to Europe. Western Tarim is a key site for studying the retreat of seawater, which was likely caused by the northward indentation of the Pamir arc and facilitated by the climatic cooling and eustatic sea level change in the Cenozoic. Here we present a new magnetostratigraphic record from the Tarim Basin that provides evidence of diachronous seawater retreat from its southwestern margin. We studied about 1360 m of well-exposed Eocene–Oligocene strata at Keliyang in the folded foreland of the West Kunlun orogen. Until now, the age of the strata has only been minimally constrained by the presence of late mid-Eocene marine fossils. Our biostratigraphic and magnetostratigraphic results demonstrate that the age of the sedimentary sequence ranges from ∼46 Ma to ∼26 Ma (mid-Eocene to late-Oligocene) and the seawater retreat at Keliyang took place at ∼40 Ma. Considering the stepwise northward indentation and uplift of the Pamir orogen, together with the other previous results, we propose that seawater retreat from the southwestern margin of the Tarim Basin was diachronous in the late Eocene ranging from 47 Ma to 40 Ma. The regional indentation, uplift and erosion of the Pamir orogen played the dominant and important role in controlling the seawater retreat from the southwestern margin of the Tarim Basin.